Palm phytoliths in subarctic Canada imply ice-free winters 48 million years ago during the late early Eocene - Siver, Peter A.; Reyes, Alberto V.; Pisera, Andrzej; Buryak, Serhiy D.; Wolfe, Alexander P. (My University, 2025)
Background and Aims: Phytoliths are microscopic siliceous structures produced in specific tissues by many plant families. The morphological features of phytoliths are diagnostic for many plant taxa and, given their inorganic composition, often become part of the fossil record. We used phytolith remains from lacustrine sediments to document the conclusive presence of Arecaceae (palms) in subarctic Canada during the late early Eocene (48 Ma). Methods: Palm phytoliths and aquatic microfossils were extracted from lacustrine mudstones in a drill core taken from the Giraffe kimberlite pipe locality using a combination of acid and oxidation treatments under low heat. Light microscopy and scanning electron microscopy were used to identify, examine and image the microfossils. Key Results: Spherical echinate-shaped palm phytoliths with cone-shaped surface tubercles, likely belonging to the tribe Trachycarpeae (subfamily Coryphoideae), were uncovered in 45 strata over a 37-m section of core. We further document in situ linear arrays of phytoliths, or stegmata, from partially decomposed palm foliage. Additionally, four aquatic organisms, largely restricted to warm subtropical and tropical localities today, were also uncovered in the same strata harbouring the palm phytoliths. Conclusions: The presence of palm phytoliths allows inference of a warm regional climate during the late early Eocene, with mean cold-month temperatures above freezing despite prolonged winter darkness. This conclusion is supported by the presence of multiple warm-water aquatic organisms that grew extensively in the maar lake. Our findings will help to document the extent and timing of perennial ice formation in the northern hemisphere during the Cenozoic. Finally, the discovery of stegmata documents that this morphological trait had evolved by early Eocene.
Keywords: Subarctic; Eocene; Giraffe pipe; kimberlite maar; palms; phytoliths; stegmata